Estudio de las modificaciones estructurales en un material ferroeléctrico por medio de dos métodos ópticos (2017)
The intensities of the Raman lines of the ceramic complex (lead titanate) have been investigated as a function of the relation of the areas of the low Raman frequency modes E(1TO) and silent. A change of tetragonal phase into cubic material was observed by Raman spectrjky. The samples were subjected to the same conditions at the time of making the Raman measurements. The UV-vis spectra of absorption suggested a change in energy levels with increasing concentration of lanthanum element (La). This study’s intention is to observe structural changes in the material by means of Raman intensities without using the traditional central position of the peak width in the bands.